Fear of missing out and cyberloafing among college students: Fear of missing out dan cyberloafing pada mahasiswa-mahasiswi - Dwifarilan Filadelfia Silalahi Silalahi; Rika Eliana (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2020)
English This research examines the effects of fear of missing out on cyberloafing. Individuals who experience fear of missing out are afraid to miss a pleasant experience. The individual will try to stay connected with others through social media. The study hypothesized that fear of missing out would be positively related to cyberloafing, which refers to behavior of accessing the internet for non-academic activities. As expected, the results show that fear of missing out accounted for about 22 per cent of the variance of cyberloafing. Those who are more afraid of missing out tended to engage more cyberloafing than those who are less fear of missing out. Bahasa Indonesia Penelitian ini menguji efek fear of missing out pada perilaku cyberloafing. Individu yang mengalami fear of missing out takut melewatkan pengalaman yang menyenangkan. Individu akan mencoba untuk tetap terhubung dengan orang lain melalui media sosial. Studi ini berhipotesis bahwa fear of missing out akan berhubungan positif dengan cyberloafing, yang mengacu pada Perilaku mengakses internet untuk kegiatan non-akademik.Seperti yang diharapkan, hasil menunjukkan bahwa fear of missing out menyumbang sekitar 22 persen dari varian cyberloafing. Mereka yang memiliki fear of missing out tinggi cenderung terlibat lebih banyak cyberloafing daripada mereka yang memiliki fear of missing out rendah.